Individual and organizational development as interplay: An activity oriented approach - Klaus-Peter Schulz; Silke Geithner (Zeitschrift für Personalforschung (ZfP), 2010)
We see the contribution of our paper as discussing an integral perspective of individual and collective development. Considering learning and development we suggest a conceptual orientation on activity theory (Chaiklin/Hedegaard/Jensen 1999; Engeström 1987, 2001, 2005). Therefore, we see the workplace as a context where people learn through collective acting and reflecting. According to Engeström we consider learning as expansive development which is brought about through contradictions in daily work and the need to change mindsets. We will refer to two case studies in medium sized firms in the technology and automotive supply industry in Germany. Using qualitative methods of social research (participatory observation, interviews, data analysis) we have analyzed the work and learning activity of production systems. We have described the current demands of the inherent contradictions in the operational work activity. Furthermore, we describe contradictions between the requirements of work and the actual learning methods. Based on these results we develop a platform model of collaborative learning and development. – – In unserem Beitrag diskutieren wir den integralen Zusammenhang zwischen individueller und kollektiver resp. organisationaler Entwicklung. Lernen und Entwicklung wird dabei aus der Perspektive der kulturhistorischen Tätigkeitstheorie (cultural-historical activity theory) betrachtet (vgl. Chaiklin/Hedegaard/Jensen 1999; Engeström 1987, 2001, 2005). Der Arbeitsprozess ist folglich der Kontext, in dem Menschen durch gemeinsames Handeln und Reflektieren lernen. Bezugnehmend auf Engeström definieren wir Lernen als expansive Entwicklung, die durch Widersprüche in der täglichen Arbeitspraxis hervorgerufen wird und den Wandel von Denk- und Handlungsmustern erfordert. Wir diskutieren dies am Beispiel zweier deutscher mittelständischer Industrieunternehmen aus der Technologie- und Automobilzulieferbranche. Mittels Methoden der qualitativen empirischen Sozialforschung wie teilnehmende Beobachtung, Interviews und Dokumentenanalyse wurden die Arbeits- und Lernprozesse in beiden Produktionsunternehmen untersucht. Darauf aufbauend werden Widersprüche in der operativen Arbeitspraxis aufgezeigt und aktuelle Lernanforderungen abgeleitet. Auf dieser Grundlage wird ein Plattformmodell zum individuellen und kollektiven Lernen entwickelt.
Keywords: 330; individual and collective development; activity theory; workplace learning; context; expansive development; production process; Verhalten in Organisationen; Lernende Organisation; Lernen; Theorie